Mapping Hepatitis B Infection in Cap Tikus Consumers in South Minahasa, North Sulawesi - Linda Augustien Makalew; Indra Elisabet Lalangpuling; Muhammad Ali Makaminan (JURNAL INFO KESEHATAN, 2025)
Risk factors for alcohol consumption can accelerate the development of hepatitis B infection leading to liver fibrosis, cirrhosis, and even Hepatocellular Carcinoma (HCC). North Sulawesi is the second province with the highest number of alcohol drinkers in Indonesia. Cap Tikus is a traditional community drink which is traditionally made from palm tree liquid. The tradition of drinking Cap Tikus is usually done by consuming it together in the same glass; where this behavior is risky behavior for the transmission of hepatitis B infection. Therefore, this research was conducted to determine the distribution of hepatitis B infection based on the results of the HBsAg examination in the South Minahasa area. The research design is quantitative with a descriptive research type. The population of the study was Cap Tikus drinkers in six locations in South Minahasa Regency. The sample consisted of 309 respondents, found through a random sampling technique based on inclusion and exclusion criteria. The research variable was the result of the HBV examination using the Enzyme Link Immunosorbent Assay (ELISA) method. The results showed that 67.6% of respondents were in the age range of 30-50 years, and 50.1% worked as farmers. The majority of respondents (31.7%) consumed Cap Tikus 3 times a week, with an alcohol level of 45-50% as many as 47.9 respondents; 41.1% of respondents consumed 250-350 ml in one drink. The results of the ELISA reader examination showed that 4 respondents (1.3%) gave results above the cut-off value of 1.007. Based on the results of the research conducted, this study concludes that as many as 1.3% of respondents were declared positive for HBsAg through the ELISA examination and were only found in Ranomea Village, South Minahasa Regency. It is hoped that the government and health workers will be able to provide health education about the dangers of drinking alcohol excessively and educate about the risk factors for transmission of the hepatitis B virus.